The Effect of Rice Consumption, Rice Prices, and Rice Harvest Area on Dependence on Rice Imports in Indonesia in 2015-2014 - Lindy Shaliha; Aliudin Aliudin; Setiawan Sariyoga; Aris Supriyo Wibowo (JURNAL ECONOMINA, 2026)
Rice is a leading agricultural commodity in Indonesia. This is reflected in Indonesia’s position as the fourth-largest producer and consumer of rice in the world. The high demand for rice mak es its availability one of the government's priorities, which is fulfilled through various policies, including rice imports. Indonesia imports rice to ensure the availability of domestic rice stocks. This study aimed to analyze the effects of rice consumption, rice prices, and harvested paddy area on rice import dependency in Indonesia during the period 2015–2024. Data were analyzed using the Ordinary Least Squares (OLS) multiple linear regression method based on secondary data. The results show that rice consumption, rice prices, and harvested paddy area simultaneously affect rice import dependency in Indonesia. Partially, rice consumption and rice prices have a significant effect on rice import dependency, whereas harvested paddy area does not have a significant effect on rice import dependency during the 2015–2024 period.